Cyclicality in Losses on Bank Loans - Bart Keijsers; Bart Diris; Erik Kole (Tinbergen Institute, 2015)
Cyclicality in the losses of bank loans is important for bank risk management. Because loans have a different risk profile than bonds, evidence of cyclicality in bond losses need not apply to loans. Based on unique data we show that the default rate and loss given default of bank loans share a cyclical component, related to the business cycle. We infer this cycle by a new model that distinguishes loans with large and small losses, and links them to the default rate and macro variables. The loss distributions within the groups stay constant, but the fraction of loans with large losses increases during downturns. Our model implies substantial time-variation in banks' capital reserves, and helps predicting the losses.
Keywords: C32; C58; G21; G33; 330; Loss-given-default; default rates; credit risk; capital requirements; dynamic factor models